Chapter Learning in Cities to Create Sustainable Societies - PIAZZA, Roberta (Studies on Adult Learning and Education, 2023)
Cities play a leading role in addressing many of the global challenges of the 21st century. They are an important part of the 2030 Agenda for sustainable development, which assigns them multiple tasks. Cities should be committed to reducing the ecological footprint and to creating solutions that respond in a differentiated way to the challenges and opportunities in different areas of the world. The sustainable development strategies of cities have determined the definition of different urban models, focused on the need to offer citizens well-being and innovation. This contribution presents the model of learning cities (LC), cities that put learning and education at the heart of their strategies. The paper identifies some of the possible strategies to make cities more responsive to the learning needs arising from the recent pandemic crisis.